Isolation and Genomic Characterization of a Heat-Labile Enterotoxin 1-Producing Escherichia fergusonii Strain from a Human - Miki Okuno; Nami Tsuru; Shuji Yoshino; Yasuhiro Gotoh; Takeshi Yamamoto; Tetsuya Hayashi; Yoshitoshi Ogura (Microbiology Spectrum, 2023)
ABSTRACT Escherichia fergusonii strains have been isolated from patients with diarrhea, but their virulence determinant has not been well elucidated. Here, we report the first isolation of a heat-labile enterotoxin 1 (LT1)-producing E. fergusonii strain (strain 30038) from a patient in Japan. The complete genome sequence of strain 30038 was determined and subjected to comparative genomics and phylogenetic analyses with 195 publicly available genomes of E. fergusonii. In addition to strain 30038, the elt1 gene was also identified in an E. fergusonii strain that is phylogenetically distinct and which was isolated from poultry in the United Kingdom. Fine genomic comparison revealed that these two strains share comparable elt1-bearing plasmids. However, an intriguing distinction arises in strain 30038, wherein the plasmid has integrated into the chromosome via a recombination process mediated by an insertion sequence. The production of active LT1 toxin by strain 30038 was verified through an in vitro assay using cultured cells. A large plasmid carrying 11 antimicrobial resistance genes was also identified in strain 30038. Our results indicate that extensive surveillance of elt1-positive E. fergusonii strains as diarrheagenic pathogens is needed. IMPORTANCE Escherichia fergusonii, a species closely related to Escherichia coli, is known to cause sporadic conditions in humans, including diarrhea. However, the critical virulence factors in E. fergusonii clinical isolates remain to be identified. This study shows the first isolation of an E. fergusonii strain carrying the elt1 gene, which encodes heat-labile enterotoxin 1, from a patient with diarrhea. Our analysis of public databases also revealed the presence of elt1-positive E. fergusonii strains isolated from poultry in the United Kingdom. Interestingly, while the elt1 gene in the poultry isolate was present on a large plasmid, in the human isolate it was integrated into the chromosome, which may confer stability on the elt1-carrying genetic element. Our findings highlight the need for extensive surveillance of elt1-positive E. fergusonii strains in livestock animals.